Comparative Chloroplast Genomics of Seven Endangered Cypripedium Species and Phylogenetic Relationships of Orchidaceae - Zhang, Jun-Yi; Liao, Min; Cheng, Yue-Hong; Feng, Yu; Ju, Wen-Bing; Deng, Heng-Ning; Li, Xiong; Plenković-Moraj, Andelka; Xu, Bo (Frontiers in Plant Science, 2022)
The species in the genus Cypripedium (Orchidaceae) are considered endangered, mainly distributed in the temperate regions of the Northern Hemisphere, with high ornamental and economic value. Despite previous extensive studies based on both morphology and molecular data, species and sections relationships within Cypripedium remain controversial. Here, we employed two newly generated Cypripedium chloroplast genomes with five other published genomes to elucidate their genomic characteristics. The two genomes were 162,773–207,142 bp in length and contained 128–130 genes, including 82–84 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. We identified 2,192 simple sequence repeats, 786 large repeat sequences, and 7,929 variable loci. The increase of repeat sequences (simple sequence repeats and large repeat sequences) causes a significant amplification in the chloroplast genome size of Cypripedium. The expansion of the IR region led to the pseudogenization or loss of genes in the SSC region. In addition, we identified 12 highly polymorphic loci (Pi > 0.09) suitable for inferring the phylogeny of Cypripedium species. Based on data-sets of whole chloroplast genomes and protein-coding sequences, a well-supported phylogenetic tree was reconstructed, strongly supporting the five subfamilies of Orchidaceae and the genus Cypripedium as monophyletic taxa. Our findings also supported that C. palangshanense belonged to sect. Palangshanensia rather than sect. Retinervia. This study also enriched the genomic resources of Cypripedium, which may help to promote the conservation efforts of these endangered species.